Arduino Mega to Build a System for Student Evaluation and Attendance - falih, sura hasan; Ismael, Yaseen Hikmat (Sistemasi: Jurnal Sistem Informasi, 2025)
Monitoring student attendance and evaluating their performance in each lab lecture form the basis of the final evaluation at the end of the semester. These records (assessment, attendance) are stored on paper lists. Manual methods include a number of drawbacks, such as time loss, inaccurate results from human mistake, and difficulty obtaining reports when required. In order to address the problems with the manual student attendance and assessment technique, this study makes use of an Arduino Mega. In addition to assigning scores for each lab assignment, lecturers can input each student's attendance and performance rating. Together with the student's attendance record, these grades are stored in text files that may be accessed using Excel spreadsheets. The proposed approach aims to enhance information accessibility, reduce the amount of time spent on manual chores, and make it easier to obtain final evaluation results. It also reduces results accuracy, human error, and administrative overhead.